ANALYSIS OF FACTORS AFFECTING ECONOMIC GROWTH (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
One of the five priorities of the Action Strategy for the further development of Uzbekistan is to strengthen macroeconomic stability and maintain high economic growth, increase the competitiveness of the national economy, modernize agriculture and focus on further development and liberalization of the economy. accelerating development, continuing institutional and structural reforms to reduce state participation in the economy, strengthening the protection of private property rights and its priority position, stimulating the development of small business and private entrepreneurship, comprehensive and balanced socio-economic development of regions, districts and cities. Active attraction of foreign investments in the sectors and regions of the economy of the country through economic development, improvement of the investment climate [1].